Pengaruh Manajemen Risiko Kredit terhadap Profitabilitas Bank Perkreditan Rakyat di Kepulauan Riau - Serly Serly; Edy Kurniawan (Faculty of Economics, Universitas Internasional Batam, 2020)
This study is aimed to identify the effect of credit risk management on the profitability of Rural Credit Banks in Riau Islands. Measurement of profitability in this dependent variable is in a form of return on assets and there are independent variables in this study in the form of capital adequacy ratio, non-performing loans, bank size, liquidity, inefficiency, and inflation. 38 banking companies are sampled in this study, all registered in the Financial Services Authority within the 2014-2018 period. Purposing sampling method is used to determine the acquired samples. Data collection is done by researching, analyzing, and studying the financial statements of the banking and then processed with the help of the Eviews software. The results showed the capital adequacy ratio, bank size, and inefficiency has a significant negative effect on return on assets. While the liquidity variable has a significant positive effect on return on assets and non-performing loan variables, while inflation do not have a significant relationship with return on assets.